Importance of Avidity for an Endogenous Drug Carrier: An Antibody Carrier for CpG Oligonucleotides - Cheung, Roland; Cho, Moo (Molecular pharmaceutics, 2010)
In animal models, successful anticancer monotherapy with CpG oligodeoxynucleotide (ODN) has been limited to the intratumoral and peritumoral routes of administration. To overcome this limitation, we developed a delivery system utilizing an endogenous antibody as a carrier for CpG ODNs. When a 1:1 conjugate of 2,4-dinitrophenyl (DNP) to a CpG ODN was administered to tumor-bearing mice that were preimmunized against DNP, intravenous (iv) administration successfully inhibited tumor growth (Palma, E.; Cho, M. J. J. Controlled Release 2007, 120, 95−103). In the present studies, we reproduced the iv results and showed that a DNP derivative of a controlled ODN with scrambled nucleotide sequence failed in the same model. Perhaps more significantly, contralateral subcutaneous (sc) routes of administration also suppressed tumor growth. However, in a separate experiment, when the anti-DNP titer level was low, the antitumor effect was abolished, supporting the importance of the avidity involved in the complexation. With the low titer, a significant fraction of injected dose must have existed as unbound that is subject to rapid clearance. The present study justifies chemically cross-linked immune complexes such that the CpG ODN cannot dissociate in the body after administration.